1990
DOI: 10.1111/j.1365-2125.1990.tb03688.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and pharmacodynamic studies of glibenclamide in non‐ insulin dependent diabetes mellitus.

Abstract: 1 The pharmacokinetic and pharmacodynamic properties of oral glibenclamide have been studied in 31 hospitalised in-patients and 79 ambulant out-patients with diabetes mellitus. 2 Breakfast was found to have no significant influence on the kinetic behaviour of glibenclamide or on the effect of this drug on blood glucose utilisation. 3 The time course of glibenclamide kinetics after 20 mg dosing was adequately described by a two-compartment open model, yielding mean half-lives of 3.3 ± 1.5 h (t½/,X) and 9.7 ± 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 40 publications
4
46
0
Order By: Relevance
“…Significantly greater lowering of blood glucose was reported by Sartor et al (1982), while no beneficial effects on blood glucose utilisation were observed in the recent study of Coppack et al (1990). Bruce et al (1988) presented evidence in support of the importance of the timing of insulin secretion in relation to meal intake.…”
Section: Discussionmentioning
confidence: 57%
“…Significantly greater lowering of blood glucose was reported by Sartor et al (1982), while no beneficial effects on blood glucose utilisation were observed in the recent study of Coppack et al (1990). Bruce et al (1988) presented evidence in support of the importance of the timing of insulin secretion in relation to meal intake.…”
Section: Discussionmentioning
confidence: 57%
“…This infusion rate leads to local forearm glibenclamide concentrations which are similar to systemic concentrations as reached daily during the treatment of NIDDM [20,21]. In this way the effect of therapeutic glibenclamide concentrations on the forearm vasodilator response to ischaemia was assessed locally.…”
Section: Methodsmentioning
confidence: 99%
“…Because of the long half-life, high protein binding [20,21] and possible incorporation of sulphonylurea derivatives in the plasma membrane [22], randomization of placebo and glibenclamide infusion was not possible because of carry-over effects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the potential role of K ATP channels in regulation of myocardium and coronary artery, glibenclamide (10 mg) was orally administered 60 minutes before catheterization with a continuous infusion of 10% dextrose at the same time. This dose of glibenclamide will result in an estimated serum concentration of 500 nmol/L, 17 which has been shown to block myocardial and vascular K ATP channels in humans. 18 To further confirm whether IP is mandatory for estrogen-induced attenuated vasoconstriction, a group treated with estrogen immediately after the second balloon deflation was assessed.…”
Section: Subjectsmentioning
confidence: 99%